Nuevos registros de escarabajos copro-necrófagos (coleoptera: scarabaeidae: scarabaeinae) para México y Chiapas. - Navarrete Gutierrez, Darío A.; Halffter, Gonzalo (Instituto de Ecología, A.C., 2008)
Three new records for Chiapas Scarabaeinae are reported [Canthon lituratus (Germar) 1813; Uroxys platypyga Howden & Young, 1981, y Onthophagus yucatanus Delgado, Peraza & DeLoya, 2006], the first two being new also for Mexico. All were captured in a tropical rain forest. The first two species, whose distribution areas to the north widen notably, belong in biogeographical terms to the Typical Neotropical Distribution Pattern – Minimal Penetration. O. yucatanus has a different biogeographical history, and belong to the Tropical Paleoamerican Pattern.